DETERMINASI KOMUNIKASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PERUSAHAAN UMUM (PERUM) BULOG SUB-DIVRE KOTA BATAM - Wicaksono, Bayu Dimas; Ratnasari, Sri Langgeng (BENING, 2017)
This research aims to get information that communication, motivation, and work environment also these three factors to employee performance in Perusahaan Umum (Perum) Bulog SUB-DRIVE Batam City. This research categorizied as quantitative  research, statistic analysis use  Regresi Linear Berganda methode with quantitative analysis. Based on SPSS data analysis, researcher got t measurement regresi linear berganda analysis to communication variable (X1) is 2.819 with significant number 0.006, motivation variable (X2) is 2.087 with significant number 0.040, work environment variable (X3) is 2.302 with significant 0.024. Result of simultan test (F test) researcher got  value 41.243 with trusted degree 95%. Conclution for this research are first hypothesis communication have partial determination to employee performance, second hypothesis motivation have partial determination to employee performance, third hypothesis work environment have partial determination to employee performance and last hypothesis received that these three variables (communication, motivation and work environment) have partial determination to employee performance.